До питання про вплив джучидської монетної традиції на формування місцевої монетної справи в українському Подніпров’ї середини – другої половини XIV ст. - Хромова, І. (Інститут історії України НАН України, 2009)
Iryna Khromova Following the question about influence of Juchid’s own coining tradition on forming of local monetary coinage in Dnipro’s valley in the middle – the second half of the XIV-th c. The article contains the analysis of degree by distribution of original Juchid’s coins within the limits of the probed territory, and also the author’s an attempt to describe of local coinsimitations.